A tropical harpacticoid copepod, Nitocra affinis californica lang as an effective live feed for black tiger shrimp larvae Penaeus monodon fabricius - Matias-Peralta, Hazel Monica; Md. Yusoff, Fatimah; Shariff, Mohamed; Mohamed, Suhaila (Universiti Putra Malaysia Press, 2012)
Survival and specific growth rates of Penaeus monodon larvae (post-larval stages 1-15), fed with different live feeds and artificial diets, were evaluated using three different treatments, namely: i) Nitocra affinis, ii) combination of Artemia nauplii + N. affinis and iii) artificial diet. The experiment was carried out in 10-L aquaria with 30% daily water exchange for a period of 16 days. The survival rate (61%) and specific growth rate (16.7 %day-1) were highest (p<0.05) in the treatment with shrimp larvae fed with N. affinis. Likewise, the protein contents of N. affinis was found to be the highest (p<0.05) among all the diets used. The fatty acids of N. affinis was dominated by polyunsaturated fatty acids (PUFA) (22:6n3) forming 19.5% of the total PUFA identified. In fact, N. affinis contained the highest (p<0.05) amount of PUFA and the highest (p<0.05) n-3/n-6 ratio amongst the three diets. Analysis of the copepod fed shrimp showed significantly higher (p<0.05) amount of long chain PUFA, both of the n-3 and n-6 series fatty acids, when compared to the artificial diet fed larvae. The results of this study showed that N. affinis has the potential to be used as an effective live feed for P. monodon due to their high PUFA contents and broad size range (nauplii to adults) to cater for different shrimp post-larval stages.